Reduced Glutathione Decreases Cell Adhesion and Increases Cell Volume - Geloen, Alain; Berger, Emmanuelle (Archives of Clinical and Biomedical Research, 2022)
Glutathione is the most abundant thiol in animal cells. Reduced glutathione (GSH) is a major intracellular antioxidant neutralizing free radicals and detoxifying electrophiles. It plays important roles in many cellular processes, including cell differentiation, proliferation, and apoptosis. In the present study we demonstrate that extracellular concentration of reduced glutathione markedly increases cell volume within few hours, in a dose-response manner. Pre-incubation of cells with BSO, the inhibitor of γ-glutamylcysteine synthetase, responsible for the first step of intracellular glutathione synthesis, did not change the effect of reduced glutathione on cell volume, suggesting a mechanism limited to the interaction of extracellular reduced glutathione on cell membrane. Similarly, inhibition of γ-glutamylcyclotransferase involved in intracellular glutamate production, essential for intracellular production of glutathione, had no effect on the action of reduced glutathione. Oxidized glutathione exerted no effect on cell volume. Results show that GSH decreases cell adhesion resulting in an increased cell volume. Since many cell types are able to export GSH, the present results suggest that this could be a fundamental self-regulation of cell volume, giving the cells a self-control on their adhesion proteins.